Pengaruh Penerapan Modul-Modul Berbasis Spreadsheet Terhadap Nilai Statistika Mahasiswa Jurusan Akuntansi Politeknik Negeri Bali - I Made Wijana; Anak Agung Putri Suardani (JTP - Jurnal Teknologi Pendidikan, 2017)
This research aims at validating spreadsheet based statistics modules, to know results of field trials, the influence of spreadsheet based modules implementation on statistics course achievement, and student’s perceptions to the implementation of spreadsheet based statistics modules. Validation of education expert used five aspects and then followed by field trials. The results of the research show that assessment/validation of the education expert is the overall modules are categorized good and all of the seven modules are also categorized good. The overall statistical modules provide better results significantly for students who used the modules compared to students who did not use the modules. Therefore, spreadsheet based modules implementation influenced statistics course achievement of Accounting Departmen students, Bali State Polytechnic. Student’s perceptions of implementation the spreadsheet based statistics modules are the majority they said good (97.7%), very good (2.3%), pretty good (0%), less good (0%), and not good (0%) or score average of 4.2 out of 5.